Novel 5-aryloxypyrimidine SEN1576 as a candidate for the treatment of Alzheimer's disease. (8th October 2013) - O'Hare, Eugene; Scopes, David I.C.; Kim, Eun-Mee; Palmer, Philip; Spanswick, David; McMahon, Bridgeen; Amijee, Hozefa; Nerou, Edmund; Treherne, J. Mark; Jeggo, Ross
Abstract: Prefibrillar assembly of amyloid- β (A β ) is a major event underlying the development of neuropathology and dementia in Alzheimer's disease (AD). This study determined the neuroprotective properties of an orally bioavailable A β synaptotoxicity inhibitor, SEN1576. Binding of SEN1576 to monomeric A β 1–42 was measured using surface plasmon resonance. Thioflavin-T and MTT assays determined the ability of SEN1576 to block A β 1–42 -induced aggregation and reduction in cell viability, respectively. In vivo long-term potentiation (LTP) determined effects on synaptic toxicity induced by intracerebroventricular (i.c.v.) injection of cell-derived A β oligomers. An operant behavioural schedule measured effects of oral administration following i.c.v. injection of A β oligomers in normal rats. SEN1576 bound to monomeric A β 1–42, protected neuronal cells exposed to A β 1–42, reduced deficits in in vivo LTP and behaviour. SEN1576 exhibits the necessary features of a drug candidate for further development as a disease modifying treatment for the early stages of AD-like dementia.